Evaluation of produced water discharge in the Niger-Delta (2011)
Water produced during petroleum production often contains chemicals, oil and sometimes, naturally occuring radioactive materials which could harm the environment. Management, which involves significant cost and is guided by strict regulations, is normally aimed at minimizing or reducing the toxicity of discharged volumes. This study evaluated the physio-chemical properties and constituents of produced water from three selected flowstations and two oil terminals in the Niger Delta to determine the extent of compliance with standard and global best practices in the treatment and discharge. It was observed that while physio-chemical properties like pH (8.4±0.25) and BOD (6.2±2.0) were within recommended limits, oil and grease content (60±20), TDS (6200±700) and others exceedded limits. Similarly, ion concentrations of Lead, NIckel, Zinc and Sulphates were within acceptable limits while Chloride ions (4 100 ±500) exceeded limits. There is therfore the nedd to improve treatment facilities and procedures, while regulatory agencies must improve current guidelines, ensure proper monitoring and enforcing compliance.